Insider dan Outsider dalam Penafsiran: Upaya Membaca Tafsir dalam Dua Sisi Perspektif Kim Knott - Mahbub Ghozali (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2020)
This study aims to find new methods and meanings in the interpretation’s field. The finding of the method is intended to provide new insights regarding the objectivity of interpretation which is often disputed by many scholars. Based on this, this study uses qualitative methods with library research techniques. To in depth the data analysis, this study uses the insider and outsider approaches introduced by Kim Knott. This research finds that the synthesis between the interpretation of Western scholars and Islamic scholars produces a textual-historical understanding simultaneously. In the sense that the Quran is understood not only in the emphasis of the law and its sacredness, but also on its historical aspects which involve the cultural and historical structures that surround the Quran. The tendency of Western scholars to understanding the Quran in its critical aspect can suppress the subjectivity of Islam scholars interpretation which tends to be tendentious. In this context, this research concludes that the insider and outsider perspectives are not only used in Islamic studies, but also in specific aspect of Islamic studies. Therefore, the use of this perspective can be applied to other specific fields of Islam, so that an understanding of Islam can be more objective.